Detection of SARS-CoV-2 in the tears and conjunctival secretions of Coronavirus disease 2019 patients - Hüseyin Kaya; Ahmet Çalışkan; Mehmet Okul; Tuğba Sarı; İsmail Hakkı Akbudak (Journal of Infection in Developing Countries)
Introduction: Current studies suggest that tears and conjunctival secretions may be an important transmission route in coronavirus disease 2019 (COVID-19). The study aims to evaluate the presence of severe acute respiratory syndrome Coronavirus-2 (SARS-CoV-2) virus in tears and conjunctival secretion of patients with COVID-19.